Turismo e eventos : os festejos farroupilhas de Caxias do Sul-RS - Spada, Anaize (My University, 2014)
The Farroupilha week was instituted by state law to incentivize the memory of the Farroupilha Revolution, a warlike event that involved the region between 1935-1945, to be celebrated all over the state of Rio Grande do Sul. Today this event is named Festejos Farroupilhas. The theme of this paper was chosen due the proportions of this event over the years. With a public of participants estimated in three thousand people, it lasts fourteen days and offers a wide variety of internment. The aim of this study is to analyze the cultural event through its history, management and relation with tourism. From a qualitative and exploratory bias, the data were gathered through bibliography revision, documentary research, interviews and observation. In summary we can assure the event contributes to promote cultural expressions related to regional rural of cattle raising in Rio Grande do Sul – generally denominated gaúcha culture – with music and dance performances and socializing among people participating. The relations with tourism are established involving cultural tourism and citizen tourism, as suggested in the body of this paper.
A Semana Farroupilha foi instituída por lei estadual para incentivar a memória em torno da Revolução Farroupilha, evento bélico que envolveu a região entre 1935-1945, a ser comemorada em todo o Estado do Rio Grande do Sul. Hoje, esse evento recebe o nome de Festejos Farroupilhas. A escolha do tema para à presente investigação deve-se às proporções que o evento Festejos Farroupilhas apresentou nos últimos anos. Com um público participante estimado em trezentas mil pessoas, possui duração de quatorze dias e oferece diversificada programação. O estudo objetiva analisar o evento cultural no seu histórico, na gestão e relação com o turismo. De corte qualitativo e viés exploratório, os dados foram reunidos a partir de revisão bibliográfica, pesquisa documental, entrevistas e observação. Em síntese, pode-se afirmar que o evento contribui para a promoção de expressões culturais associadas ao regional rural da pecuária no Rio Grande do Sul – genericamente denominada como cultura gaúcha –, através de espetáculos musicais, dança e convívio entre as pessoas participantes. As relações com o turismo se estabelecem envolvendo o turismo cultural e o turismo-cidadão, conforme sugestões no corpo do trabalho.
Keywords: Turismo cultural -- Caxias do Sul (RS); Turismo; Folclore -- Caxias do Sul (RS)